(untitled) (University Heart Journal, 2008)
This prospective study was carried out in the coronary care unit, department of cardiology in National Institute of Cardiovascular Diseases, Dhaka, during the period of July 2007 to December 2007. Sixty consecutive patients with acute myocardial infarction below 40 years of age, subjected to coronary angiogram were enrolled with some inclusion and exclusion criteria to evaluate the risk factors and pattern of coronary artery disease in young patients with myocardial infraction. The age range of the study patients was 14-39 years with mean age of 29.07 Â± 3.45 years. 56 (93.33%) patients were male and 4 (6.67%) patients were female. It was evident that commonest risk factor was smoking 73.33%. Other risk factors include dyslipidaemia 53.33%, hypertension 41.67%, hyperhomocystinaemia 25%, family history of IHD in 13.33% patients and diabetes 6.67%. Coronary artery diseases present in 91.67% patients. 72.73% patients had single vessel disease, 18.18% patients had double vessel disease and 9.09% patients had triple vessel disease. Left anterior descending artery involved in 80% patients, left circumflex artery involved in 27.27% patients and right coronary artery involved in 29.09% patients. In conclusion, acute myocardial infraction in young patients is most commonly seen in males and most frequent risk factor is smoking. Majority patients has single vessel disease and most frequently involve vessel is LAD. Â University Heart Journal Vol.4(1) January 2008